Distribution and characteristics of human papilloma virus infection genotyping in women in Changchun area - Pingping Zhou; Zhenwu Du; Xuyuan Qin; Jiaxin Chen; Guizhen Zhang (Guoji laonian yixue zazhi, 2025)
[Objective] To analyze the infection and genotyping characteristics of human papilloma virus(HPV) in women in Changchun area, and provide a theoretical basis for the prevention and treatment of HPV infection induced diseases in this area. [Methods] A total of 6 750 women who went to Changchun Cancer Hospital from October 2020 to March 2024 for the first HPV type test were selected as the study subjects, the HPV infection and the characteristics of different genotyping infections were analyzed. [Results] The positive rate of HPV infection in 6 750 samples was 20.46%(1 381/6 750), and the high-risk HPV infection rate was 18.16%(1 226/6 750).The single genotyping HPV infection was the main type, and there were multiplemixed genotyping infection(2-6 types).The top five genotyping of high-risk HPV detection rate were HPV16, HPV52, HPV58, HPV51 and HPV53.The high-risk infection rate was the highest in older people over 60 years old [25.28%(135/534)] , followed by 15-30 years old [24.26% (163/672)] .The infection rate in these two ages was significantly higher than that in other ages, and the difference was statistically significant(P<0.05).The mixed infection rate of HPV genotypings in older people over 60 years old was 8.43% (45/534), which was significantly higher than those in other age groups(P<0.05). [Conclusion] Among female HPV infection patients in Changchun area, the proportion of pure high-risk type is relatively high, and the proportion of high-risk type infection patients is the highest among those over 60 years old.Elderly people over 60 years old are the key focus of HPV infection prevention and control in this area.